A pathway to personal, population and planetary health for dietitians and nutrition professionals - Kristen L. MacKenzie‐Shalders; Liza Barbour; Karen Charlton; Gregory R. Cox; Mark Lawrence; Sandra Murray; Kylie Newberry; Nicole M. Senior; Rosemary Stanton; Angela M. Tagtow (Wiley, 2023)
Abstract Background Earth and all its inhabitants are threatened by a planetary crisis; including climate change, deforestation, biodiversity loss and pollution. Dietitians and nutrition professionals have a responsibility to lead transformational change in contemporary food and health systems to help mitigate this crisis. The study aims to develop a conceptual framework to support dietitians towards personal, population and planetary health. Methods Non‐empirical methods were used by the co‐researchers to explore and explain the application of an international framework 'Next‐Generation Solutions to Address Adaptive Challenges in Dietetics Practice: The I + PSE Conceptual Framework for Action'. Results A non‐sequential pathway guide to personal, population and planetary health for nutrition professionals was developed including several key guiding principles of Agency, Action, Ascension, Alignment, Alliance and Allyship, and Advocacy and Activism. Each guiding principle features descriptors and descriptions to enhance dietitian and nutrition professional Agency (i.e. vision, self‐belief, confidence, strength and responsibility), Action (i.e. start, shift, translate, achieve and commit), Ascension (i.e. build, overcome, manage, challenge and progress), Alignment (i.e. leadership, transparency, diplomacy, values and systems), Alliance and Allyship (i.e. support, collaborate, represent, community and citizenship) and Advocacy and Activism (i.e. disrupt, co‐design, transform, empower and urgency). The framework and its descriptors support enhanced understanding and are modifiable and flexible in their application to guide the participation of dietitians and nutrition professionals in transformational change in personal, population and planetary health. This guide acknowledges that First Nations knowledge and customs are important to current and future work within this field. Conclusions Alongside the international body of work progressing in this field, this framework and visual guide will support dietitians and nutrition professionals to achieve urgent, transformational change in personal, population and planetary health.